Estudo comparativo de coagulantes sulfato de alumínio e tanino no tratamento de efluente gráfico - Ferreira, Suellen Ticiane (2023)
The effluents from the flexography process are composed of dyes, solvents and additives, present in the printing inks. They should be treated to avoid environmental impacts on receiving bodies. Therefore, this study aimed to evaluate the performance of the physical-chemical treatment with two coagulants (aluminum sulfate and tannin) on a laboratory scale compared to treatment on an industrial scale, in the removal of COD, TOC, EA and turbidity for the generation of treated effluent for reuse purposes. The experimental compound planning carried out in Jar Test, were performed by the star 23 type experimental compound planning varying pH, concentration of chemicals (Cco) and settling time (ST) and analyzed by R software. The best conditions for aluminum sulfate were pH 9, Cco 1750 mg.L-1 and ST of 35 min, while for tannin it was pH 9, Cco 400 mg.L-1 and ST of 45 min. Removals of COD, TOC, EA and turbidity of 21%, 20%, 34% and 100% with aluminum sulfate. Besides, the best performance of treatment using tannin was 37%, 18%, 92%, 91% removals of COD, TOC, EA and turbidity respectively. The variability of the evaluated samples however, hindered obtaining a predicted model and its possible validation. The proposed treatments, however, did not overcome the current industrial performance, being recommended the installation of a preliminary equalization process in order to improve performance. The results, however, are promising for the possibility of partial reuse of the treated effluent for pre-washing flexography cylinders, where 10% reuse would impact approximately R$ 5000/year.